Is dual-energy computed tomography helpful to determinate the ferromagnetic property of bullets?. (December 2018) - Diallo, I.; Auffret, M.; Deloire, L.; Saccardy, C.; Aho, S.; Ben Salem, D.
Highlights: The determination of the ferromagnetic properties of the retained projectiles is necessary before considering an MRI examination. -Dual-Energy Computed Tomography (DECT) may play a role by testing the interaction of X ray photon with metal. Dual-Energy Index (DEI) were significantly lower in the core of ferromagnetic projectiles than those of non-ferromagnetic ones Abstract: Background: Gunshot injuries are frequent and may result in retained ballistic projectiles or fragments, this is why it is crucial to determinate the ferromagnetic property of retained projectiles if an MRI is considered. Purpose: The goal of this ex vivo study was to determine if Dual-Energy Computed Tomography (DECT) can discriminate ferromagnetic bullets from non-ferromagnetic bullets. Material and Methods: Twelve different bullets, placed in the center of the scanner on a gelatin phantom, underwent DECT evaluation. These projectiles were both ancient bullets from the 19Th century (eg. 8 mm 1890 ECP) and recent bullets from the late 20th century (eg. 9 mm Lüger; 7.92 mm Mauser; 7 mm sport carabin). Two independent radiologists who were blinded to the properties of bullets performed all measurement on an external workstation with extended CT scale. Regions of interest (ROI) were placed in the core of each projectile. From these data, a dual-energy index (DEI) was calculated. A bootstrap method with a p value of less than 0.05 was used to demote statistical significance. Results: Five bullets were ferromagnetic and seven were non-ferromagnetic. The DEI calculated were significantly (p < 0.05) different between the ferromagnetic and non-ferromagnetic projectiles. There were no significant difference (p > 0.05) for intrareader and interreader agreement analysis. Conclusion: DECT, found a difference between this ferromagnetic and non-ferromagnetic bullets samples using an extended HU, but because of several limitations in this study there is no cut-off DEI value to differentiate these two groups of bullets.